Validated Spectrophotometric Method for Estimation of Olmesartan Medoxomil in Pharmaceutical Formulation - Al Masud, Abdullah; Rahman, Md Mahfuzur; Hasan, Moynul; Ripon, Md Kamal Hossain; Khan, Ahsanur Rahman; Islam, Md Rabiul; Sarkar, Md Raihan (International Journal of Pharmaceutical and Life Sciences, 2012)
A simple, sensitive and accurate spectrophotometric method has been developed for the deterrmination of Olmesartan Medoxomil in raw material and tablets. The ?max of Olmesartan Medoxomil was found to be 256 nm. The linear dynamic response was found to be in the concentration range of 4-14 ?g/mL and coefficient of correlation was found to be 0.9993. The %RSD value was below 2.0 for intraday and interday precision indicated that the method was highly precise. The LOD and LOQ were found to be 0.105 and 0.3045 ?g/mL respectively which revealed that method was highly sensitive. The percentage recovery value was higher than 100 %, indicating the accuracy of the method and absence of interference of the excipients present in the formulation. The proposed method was simple, fast, accurate, precise and reproducible and hence can be applied for routine quality control analysis of Olmesartan Medoxomil in bulk and pharmaceutical formulations. DOI: http://dx.doi.org/10.3329/ijpls.v1i3.12980 International Journal of Pharmaceutical and Life Sciences Vol.1(3) 2012